Self-Directed Learning and E-Learning as Congenial Fellows? An Empirical Comparison Study in the Geographical Teacher Training - Kanwischer, Detlef (Journal of Geography Education, 2006)
The shift of paradigm in education goes along with the well-analyzed and critically incorporated paradigmatic shift in society, economy and technology. The demand for "lifelong learning" coincides with a cultural change in teaching and learning processes. In the course of the discussion on the design of different teaching settings, two main teaching patterns come to the fore: self-directed learning and E-learning. These are regarded to be mutual dependent. In short, their relation can be described in these terms: As a consequence of the requirement for a more profound education the methods to support the teaching process have to be improved urgently. Teachers necessarily need to respond to modified presuppositions. However, common guidelines for suitable arrangements concerning the teacher-pupil interaction in self-directed learning processes in E-learning periods are still missing. Furthermore it is hardly known which action patterns, experiences and driving forces influence the teacher's attitude towards and approval of E-learning. These topics are at the focus of interest in an action-research work on training units for geography teachers. Regarding the results of the empirical study it cannot be doubted at all, that E-learning is not likely to replace traditional forms of (presence) learning in the short or medium run. Many teachers might not be able to cope with new demands on the spot. If the chance of self-directed learning and E-learning is meant to be taken by teachers rather than to be ignored, negative experiences must be excluded. In any case, two measures can be taken to cope with the situation: promote positive experiences that teachers have had so far and cater for the teachers' needs for social and emotional events and relations.